Validitas dan Reliabilitas Kuesioner Faktor Penyebab Terjadinya Perilaku Kekerasan terhadap Perawat dilayanan Kesehatan - Heryyanoor; Restu Pertiwi, Melinda; Hardiyanti, Diana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Instruments play an important role in determining better research results. One form of instrument is a questionnaire, which is the accuracy and reliability of which researchers should pay more attention to. This study tested the validity and reliability of a research questionnaire on the factors that cause violent behavior toward nurses in health services. A descriptive research design was used with a sample of 45 respondents, using purposive random sampling. The questionnaire variables and instruments consist of 88 statements with a Likert scale consisting of nurses' therapeutic communication attitudes 10 statements; nurses' self-concept six statements; perceptions related to nurses' workload 14 statements; nurses' job satisfaction 15 statements; perceptions pertaining to nurses' work experience 12 statements, quality of service 22 statements, and incidents of violent behavior by nurses nine statements. Analysis of validity and reliability tests with a computer program: the results are expressed based on the validity and reliability test results table. The statement is said to be valid if r results > r table person product moment df = n-2 = 45-2 = 43 with a significance level of 5%, so the r table value is 0.301. At the same time, reliability is stated if the Cronbach's alpha value is > 0.6. The research results showed that 77 statements (87.5%) were valid, and 11 statements (12.5%) were invalid. The average level of variable reliability is 0.822, which is included in the good category. The conclusions of the questionnaire were declared valid and reliable for use in research.